Dampak Pandemi Covid-19 Terhadap Tingkat Partisipasi Masyarakat di Pemilukada Kabupaten Buol Tahun 2020 - Sukmawati (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2021)
In the current condition of the Covid19 pandemic, the General Election of Regional Head (Pemilukada) will simultaneously be implemented throughout Indonesia by implementing a strict health protocol. This is because Indonesia is a democracy that guarantees its citizens participating both directly or through representatives in the formulation, development and law making. Various mechanisms have been carried out well like applying 3 m namely hand washing, wearing masks and keeping the distance of the convenience and safety of voters in each polling station (TPS). But in fact, the level of community participation in the area, especially in Buol Regency, is very minimal and far from expectations because the community is reluctant to come to the polling station to use its voting rights due to fears to be infected by the Covid-19 virus.